Selected Topics in Plasma Physics - Singh, Sukhmander (IntechOpen, 2020)
This book is planned to introduce the advances topics of plasma physics for research scholars and postgraduate students. This book deals with basic concepts in plasma physics, non-equilibrium plasma modeling, space plasma applications, and plasma diagnostics. It also provides an overview of the linear and nonlinear aspects of plasma physics. Chapters cover such topics as plasma application in space propulsion, microwave-plasma interaction, plasma antennas, solitary waves, and plasma diagnostic techniques.